Study of The Efficiency of Using Pseudomonas Spp in Wastewater Treatment - Abdul Amir, Abbas Hussein (Universitas Muhammadiyah Sidoarjo, 2025)
The search for easy and effective wastewater treatment options is essential in light of the worsening water pollution problem with increasing population and industrialization. Isolation of Pseudomonas aeruginosa bacteria from sewage-contaminated water and evaluation of its efficiency in removing these pollutants. The capacity of Pseudomonas aeruginosa strains to remove chemical contaminants and heavy metals under several environmental conditions was examined after they were isolated from polluted wastewater and genetically characterized. Advanced genetic testing and regular water analyses were used to assess their effectiveness. The performance of several drinking water treatment plants was also measured in terms of nitrate removal, with varying results depending on the substrates tested. removal were more than The pollutant removal exceeded 87% for nickel, which was the highest, while it was 30% for nitrate, which was the lowest. These results indicate the potential use of this bacteria as a potential environmentally friendly wastewater treatment organism, and its effectiveness could be significantly improved with simple modifications to treatment conditions. Highlights: Pseudomonas aeruginosa effectively removed up to 70% of organic pollutants (COD) and over 60% of nitrogen compounds from wastewater. The bacteria showed high heavy metal removal efficiency, with 87.2% for nickel and 77.5% for zinc. Nitrate removal was the lowest (30.3%), highlighting the need for optimized treatment conditions to improve efficiency.